2021
DOI: 10.1515/epoly-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable nanocomposite films based on SiO2 and biodegradable poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) for food packaging

Abstract: Sustainable nanocomposites with transparent, biodegradable, and enhanced mechanical and barrier properties were prepared by the incorporation of SiO2 into poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) films and subsequent solvent casting. The crystallinity of composites could be increased by 67% with appropriate contents of SiO2, which proved that SiO2 were effective nucleating agents for PHBH. And it was worth mentioning that the contributions of SiO2 to the crystallization and thermal stability of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…It was found that the bare PHBH showed a rough structure with holes (Figure 8(a)). 22 After the addition of different amounts of SiO 2 into PHBH matrix, homogeneous dispersion was observed, even though, a higher amount of SiO 2 content increased the aggregation owing to the high surface polarity of SiO 2 (Figure 8(f)), leading to less homogenous film formation.…”
Section: Characterization Of Bionanocompositesmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that the bare PHBH showed a rough structure with holes (Figure 8(a)). 22 After the addition of different amounts of SiO 2 into PHBH matrix, homogeneous dispersion was observed, even though, a higher amount of SiO 2 content increased the aggregation owing to the high surface polarity of SiO 2 (Figure 8(f)), leading to less homogenous film formation.…”
Section: Characterization Of Bionanocompositesmentioning
confidence: 97%
“…Cross-section of (a) PHBH, (b) 0.5-SiO2/P, (c) 1-SiO2/P, (d) 1.5-SiO2/P, (e) 2-SiO2/P and (f) 2.5-SiO2/P taken by SEM. (Reprint from Ref 22. ).…”
mentioning
confidence: 99%
“…Various combination of co-polymer will produce biopolymer with various physical properties. For example, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate [P(HB-co-HHx)] is extensively ameliorate for food packaging [61][62][63], consumables, medical devices and tissue engineering due to its mechanical properties, excellent biocompatibility and biodegradability [64][65][66]. PHB has similar physical properties as polypropylene, however, it is brittle and lack of toughness.…”
Section: Phb and P(hb-co-hhx)mentioning
confidence: 99%
“…[5] As a result, researchers are looking for a bio-sourced, biodegradable material that can replace traditional plastics in single-use applications. [6][7][8][9] Bio-sourced polysaccharides, which are one of the most available raw materials in nature, have sparked a lot of interest in replacing single-use plastics. Their abundant availability, combined with their biodegradability, nontoxicity, and biocompatibility, can solve the aforementioned issue.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] As a result, researchers are looking for a bio‐sourced, biodegradable material that can replace traditional plastics in single‐use applications. [ 6–9 ]…”
Section: Introductionmentioning
confidence: 99%